2012
DOI: 10.1038/ejhg.2012.136
|View full text |Cite
|
Sign up to set email alerts
|

MLH1 methylation screening is effective in identifying epimutation carriers

Abstract: Recently, constitutional MLH1 epimutations have been identified in a subset of Lynch syndrome (LS) cases. The aim of this study was the identification of patients harboring constitutional MLH1 epimutations in a set of 34 patients with a clinical suspicion of LS, MLH1-methylated tumors and non-detected germline mutations in mismatch repair (MMR) genes. MLH1 promoter methylation was analyzed in lymphocyte DNA samples by MS-MLPA (Methylation-specific multiplex ligation-dependent probe amplification). Confirmation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 35 publications
9
38
0
Order By: Relevance
“…The low frequency of constitutional epimutations, analytical limitations and uncertainty regarding the penetrance of these epimutations, their expression and their mode of inheritance may underlie such suboptimal diagnosis. Our results confirm previous reports of a prevalence of constitutional epimutations of approximately 10% in cases fulfilling the rBG with loss of MLH1 expression and no pathogenic mutations according to standard genetic testing 4 5 11 13. These findings strongly support the routine evaluation of constitutional epimutations in cases fulfilling the rBG that lack MLH1 expression and display MLH1 hypermethylation before considering them to be sporadic CRC cases.…”
Section: Discussionsupporting
confidence: 90%
“…The low frequency of constitutional epimutations, analytical limitations and uncertainty regarding the penetrance of these epimutations, their expression and their mode of inheritance may underlie such suboptimal diagnosis. Our results confirm previous reports of a prevalence of constitutional epimutations of approximately 10% in cases fulfilling the rBG with loss of MLH1 expression and no pathogenic mutations according to standard genetic testing 4 5 11 13. These findings strongly support the routine evaluation of constitutional epimutations in cases fulfilling the rBG that lack MLH1 expression and display MLH1 hypermethylation before considering them to be sporadic CRC cases.…”
Section: Discussionsupporting
confidence: 90%
“…11 These cases have tended to be sporadic due to the spontaneous origination of the epimutation in carriers and its subsequent eradication in the germline. [12][13][14][15] However, a handful of familial cases with an MLH1 epimutation have been reported in which transmission of the epimutation between generations has been shown to occur in both non-Mendelian 14 and autosomal dominant patterns, with the latter linked to localized cis-acting genetic anomalies. 16,17 In a Caucasian family from Western Australia (WA Family 16), dominant transmission of a mosaic MLH1 epimutation was demonstrated through three successive generations linked to a particular haplotype bearing two single-nucleotide variants (SNVs) in tandem; promoter substitution c. À27C4A and missense variant c.85G4T (p.A29S) (according to coding reference sequence NM_000249.2).…”
Section: Introductionmentioning
confidence: 99%
“…Mangold et al found germline mutations of MLH1 or MSH2 in 62% of patients who fulfilled the revised Bethesda guidelines and had MSI-H [28]. Colorectal cancer patients with suspected Lynch syndrome, who were selected for epimutation tests because of negative germline tests for MMR genes, had MSI and IHC loss of MLH1 due to epimutation at rates of 3%–10% [11,13,14,16,17,29,30,31,32,33]. The current study suggests that similar findings may occur in endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of mature spermatozoa from male MLH1 epimutation carriers have shown that MLH1 methylation is absent in spermatozoa, while methylation is present soma-wide [13,31,36,37]. Constitutional epimutation is the term describing the epigenetic change found in somatic tissues, but is absent or erased in the germline.…”
Section: Discussionmentioning
confidence: 99%